2015
DOI: 10.1016/j.joca.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the variation of loading frequency on surface failure of bovine articular cartilage

Abstract: The increase in crack length with loading frequency indicated that, increased loading frequency can result in cartilage becoming damaged. The results of this study have implications in the early stages of osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
60
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 53 publications
(74 reference statements)
10
60
1
Order By: Relevance
“…However, the same peak load and number of cycles at 1 Hz did not create any cracks. This observation is consistent with previous findings that following 10,000 cycles of compressive stress in the range of between ~ 3 and 7.5 MPa, through an indenter, produced surface cracks on cartilage [30]. It should be noted that both this current study and previous study by Sadeghi et al [30] tested cartilage-on-bone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the same peak load and number of cycles at 1 Hz did not create any cracks. This observation is consistent with previous findings that following 10,000 cycles of compressive stress in the range of between ~ 3 and 7.5 MPa, through an indenter, produced surface cracks on cartilage [30]. It should be noted that both this current study and previous study by Sadeghi et al [30] tested cartilage-on-bone.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with previous findings that following 10,000 cycles of compressive stress in the range of between ~ 3 and 7.5 MPa, through an indenter, produced surface cracks on cartilage [30]. It should be noted that both this current study and previous study by Sadeghi et al [30] tested cartilage-on-bone. The physical behaviour of cartilage when on and off-bone was suggested to be different [39] because of the restraining effects of the underlying bone to cartilage [40, 41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although this simplified model assumed one directional fluid flow neglecting the flow through the disc lateral surface, the obtained velocity value is comparable to the interstitial fluid velocity of 3.14 × 10 −10 m/s reported for a damaged articular cartilage tissue under a rolling load. 87 This result indicates again relevance of the bioreactor conditions applied.…”
Section: Discussionmentioning
confidence: 77%
“…The first signs of cartilage degeneration are proteoglycan (PG) loss and collagen degeneration, leading to higher permeability of the tissue . The mechanisms driving these changes during the progression of OA are still not fully understood, but it has been suggested that excessive stresses, strains, and cumulative loadings in cartilage play a major role …”
mentioning
confidence: 99%